Dinamika Pengelolaan Pasar Lubuk Alung sebagai Pasar Adat Dibawah pengelolaan Datuak Marajo 2018-2025 - Meli Darmayati; Abdul Salam (Jurnal Kronologi, 2026)
Lubuk Alung Market is a market located in Lubuk Alung sub-district, Padang Pariaman,West Sumatra. This market is known by the local people as Nagari Market, but in realityLubuk Alung Market is not a nagari market but a traditional market. This study aims toanalyze the customary leadership system implemented in the management of the LubukAlung market by Datuak Marajo as the market head for 2019-2025, as well as to analyzethe parties involved in the management of the Lubuk Alung market. This research employsa historical method with several stages: heuristics, source criticism, interpretation, andhistoriography. To obtain data, the author collected data from various official sources,such as previous archives, newspapers, previous research, books, and articles, as well asinterviews with Datuak Marajo and other parties involved in the management of thistraditional market. The results of this study indicate that Lubuk Alung Market is atraditional market that has been managed from generation to generation by traditionalfigures who have a relationship with the ownership of the customary land where the marketstands. Datuak Marajo was the head of the Lubuk Alung market management, managingit from 2019 to the present. During Datuak Marajo's tenure, the management of thetraditional market faced several challenges, including land preservation, fires, and a nearexecutionof the market. Datuak Marajo is the head of the Lubuk Alung marketmanagement, managing the Lubuk Alung market from 2019 to the present. Themanagement of the traditional market during Datuak Marajo's reign faced severalchallenges, such as land disputes, fires, and a near-execution of the market. These conflictchallenges certainly resulted in divisions between the Niniak Mamak who managed theLubuk Alung market, traders, KAI, and other parties. Datuak Marajo still leads the LubukAlung market even though he only served for 5 years, but due to ongoing land disputes andthe absence of Datuak Marajo's nephew who could replace his leadership.